2022
DOI: 10.1073/pnas.2107942119
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ imaging of self and other in medial prefrontal cortex during social dominance interactions in a tube test

Abstract: The study of social dominance interactions between animals offers a window onto the decision-making involved in establishing dominance hierarchies and an opportunity to examine changes in social behavior observed in certain neurogenetic disorders. Competitive social interactions, such as in the widely used tube test, reflect this decision-making. Previous studies have focused on the different patterns of behavior seen in the dominant and submissive animal, neural correlates of effortful behavior believed to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…Additionally, we discovered that the mPFC-NAc neurons encode social winning behaviors such as push and resistance, while the mPFC-VTA neurons encode social losing behaviors such as retreat (Figure 3). These results strongly support previous findings that one-third of push-encoding mPFC neurons are also activated when a mouse resists an opponent’s pushes 20 and retreat behavior is encoded in distinct neuronal subpopulations in the mPFC 24,25 . However, a discrepancy exists between our findings and those of previous study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Additionally, we discovered that the mPFC-NAc neurons encode social winning behaviors such as push and resistance, while the mPFC-VTA neurons encode social losing behaviors such as retreat (Figure 3). These results strongly support previous findings that one-third of push-encoding mPFC neurons are also activated when a mouse resists an opponent’s pushes 20 and retreat behavior is encoded in distinct neuronal subpopulations in the mPFC 24,25 . However, a discrepancy exists between our findings and those of previous study.…”
Section: Discussionsupporting
confidence: 91%
“…However, a discrepancy exists between our findings and those of previous study. Although other researchers have reported that distinct mPFC neurons encode push and approach 24,25 , our findings show that these two behaviors enhance the activity of mPFC-NAc neurons (Figure 3D, E, L, S3A, B, Q). This may be due to the restriction of fiber photometry, which measures the activity of neuronal populations without considering cellular heterogeneity.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The prefrontal cortex (PFC), a high-order cortex, which plays a vital role in consciousness and cognitive control, is involved in the eCBs associated with recovery from anesthesia (Miller, 2000 ; Miller and Cohen, 2001 ; Zhong et al, 2017 ). Furthermore, the prelimbic prefrontal cortex (PrL), the important part of ventromedial PFC, has been attracting more and more attention in cognition, recognition, learning, and memory (Brockett et al, 2022 ; Cardoso-Cruz et al, 2022 ; Garcia-Font et al, 2022 ). Recent research also showed that increased pro-inflammatory cytokines in the PFC induced by lipopolysaccharide (LPS) led to delirium-like behavior in mice (Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%